Theaching literary translation with tales and albums for youth - Laso y León, ESther (Ondina - Ondine, 2020)
In this paper we will try to demonstrate the interest of tales and picture-books for young people in teaching/learning literary translation. To this end, we will analyse a pedagogical experiment conducted from 2014 to 2017.Keywords : literary language, tales, picture-books, teaching literary translation